Antiicing Properties of Bioinspired Liquid‐Infused Double‐Layer Surface with Internal Wetting Transport Ability. Issue 10 (7th April 2019) - Guo, Zhenyu; Gao, Chunlei; Li, Jinghui; Liu, Yufang; Zheng, Yongmei
Abstract: Inspired by the poison dart frog skin that secretes functional liquid after being stimulated, a liquid‐infused double‐layer surface (LDS) is designed by integrating superhydrophobic layer with liquid‐infused layer. Both layers generate the wettability gradient to drive tiny condensed droplet into the liquid‐infused layer, and the liquid‐infused layer would effectively lower the freezing point for nonicing. Especially, the internal wetting transport ability appears between both layers, greatly reducing icing possibility of the surface, i.e., the tiny condensed droplets in the micropores can be transported to liquid‐infused layer with nonfrozen properties. Thus, the surface of LDS thereby keeps superhydrophobic property for antiicing and antifrosting in a long term. This design makes LDS achieve excellent antiicing and antifrosting properties against cold environments with high humidity. And it may be significant for such materials to be extended into some realms, e.g., antiicing in aviation and power for long‐term durability in cold and high moisture environment. Abstract : A bioinspired bilayer fibrous surface achieves both robust antiicing and antifrosting performances at cold humid environment.